Transferring ownership of public housing to existing tenants: A mechanism design approach - Tommy Andersson; Lars Ehlers; Lars-Gunnar Svensson (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2015)
This paper explores situations where tenants in public houses, in a specific neighborhood, are given the legislated right to buy the houses they live in or can choose to remain in their houses and pay the regulated rent. This type of legislation has been passed in many European countries in the last 30-35 years (the U.K. Housing Act 1980 is a leading example). The main objective with this type of legislation is to transfer the ownership of the houses from the public authority to the tenants. To achieve this goal, selling prices of the public houses are typically heavily subsidized. The legislating body then faces a tradeoff between achieving the goals of the legislation and allocating the houses efficiently. This paper investigates this specific tradeoff and identifies an allocation rule that is individually rational, equilibrium selecting, and group non-manipulable in a restricted preference domain that contains "almost all" preference profiles. In this restricted domain, the identified rule is the equilibrium selecting rule that transfers the maximum number of ownerships from the public authority to the tenants. This rule is preferred to the current U.K. system by both the existing tenants and the public authority. Finally, a dynamic process for finding the outcome of the identified rule, in a finite number of steps, is provided.
Keywords: C71; C78; D71; D78; 330; public housing; existing tenants; equilibrium; minimum equilibrium prices; maximum trade; group non-manipulability; dynamic price process